2000
DOI: 10.1046/j.1365-2265.2000.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced vitamin D receptor expression in parathyroid adenomas: implications for pathogenesis

Abstract: (1) There is reduction of vitamin D receptor expression in almost all cells in parathyroid adenomas. This defect was probably present in the founder cell of the tumour clone in the majority of cases. Since mutations in the vitamin D receptor gene have been sought but not found, possible explanations include inhibition of vitamin D receptor gene transcription, decreased amount of the corresponding mRNA, or failure of normal translation. (2) Reduction in calcium sensing receptor could be either the primary defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 43 publications
6
23
1
1
Order By: Relevance
“…The downregulation of VDR expression in parathyroid adenomas in patients with symptomatic PHPT is similar to previous report of probably mild PHPT patients (12). Because the normal parathyroid tissues in our samples showed both nuclear and cytoplasmic positivity, we separately assessed nuclear and cytoplasmic VDR expression and found decreased expression of VDR at both cellular locations in parathyroid adenomas.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The downregulation of VDR expression in parathyroid adenomas in patients with symptomatic PHPT is similar to previous report of probably mild PHPT patients (12). Because the normal parathyroid tissues in our samples showed both nuclear and cytoplasmic positivity, we separately assessed nuclear and cytoplasmic VDR expression and found decreased expression of VDR at both cellular locations in parathyroid adenomas.…”
Section: Discussionsupporting
confidence: 63%
“…Representative paraffin blocks were retrieved and immunostained as previously reported (12,22) RNA extraction and cDNA synthesis Briefly, each tissue sample was crushed in 1 ml TRI reagent (Sigma-Aldrich). After chloroform addition, the aqueous and organic phases were separated by centrifugation.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Initial reports showed that vitamin D uptake was higher in parathyroid adenomas compared to cases of secondary hyperplasia and that VDR levels were similar in adenomas compared to normal tissue (Korkor, 1987, Trydal et al, 1992. More recent studies showed reduced levels of VDR mRNA in parathyroid adenomas and reduced immunostaining (Carling et al, 2000, Sudhaker Rao et al, 2000. In our series, mean VDR mRNA levels (as determined by quantitative RT-PCR) did not differ significantly between the three groups.…”
Section: Altered Expression Of Vdr Target Genes In Men1 Parathyroid Asupporting
confidence: 42%
“…VDR null or 1-hydroxylase null (unable to synthesize 1,25(OH) 2 D 3 ) mice develop parathyroid hyperplasia (Bouillon et al, 2008). VDR gene polymorphisms are associated with primary hyperparathyroidism and alterations of VDR mRNA and protein levels have been reported to occur in parathyroid adenomas (Carling et al, 1995, Carling et al, 2000, Sudhaker Rao et al, 2000. Parathyroid adenomas are the most common manifestation of MEN1, with a penetrance of almost 100%.…”
Section: Introductionmentioning
confidence: 99%